A study to determine the incidence of estrogen receptor (ER) and progesterone receptor (PR) expression in different histological grades of breast cancer. (June 2014) - Sarmah, Amrit; Das, Arabinda; Datta, Debashis
Abstract : Carcinoma of the breast is the most common non-skin malignancy in women and second most common cause of death due to cancer in females. Breast cancer is a heterogeneous disease with varied morphological appearances, molecular features, behavior, and response to therapy. This study was conducted with the aim of analysis of steroid receptor status in breast cancer and its association with other prognostic factors of breast cancer such as histological grade, tumor size, and axillary lymph node status. Fifty patients with the diagnosis of breast cancer were included in this study. Detailed clinical and histopathologic data were recorded in all cases. Estrogen receptor (ER) and progesterone receptor (PR) status was evaluated by immunohistochemistry. Histological grading was done with Nottingham modification of the Bloom and Richardson method. Fisher's exact test and chi-square test was used for statistical analysis. On immunohistochemical staining, 44% cases proved to be ER positive and 48% cases PR positive. The results from the present study in India documented low ER and PR positivity in breast cancer in comparison to results from the western world. An inverse relation was found between hormone receptor (HR) status and histological grading, but no statistically significant relationship was noted between HR expression and tumor size and lymph node status.